2009
DOI: 10.1007/s10637-009-9351-4
|View full text |Cite
|
Sign up to set email alerts
|

Complete remission of ovarian cancer induced intractable malignant ascites with intraperitoneal bevacizumab. Immunological observations and a literature review

Abstract: Malignant ascites resistant to conventional drugs frequently affects ovarian cancer patients at the end of life. Here we report the case of a patient who benefited from complete resolution of ascites after low dose intraperitoneal administration of bevacizumab. Immunological analyses showed an initial increase in proportion and function of CD8(+) effector T cells and a reduction of circulating T(reg) cells. A review of the current literature regarding bevacizumab in ovarian cancer is reported. Bevacizumab has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 47 publications
1
24
0
1
Order By: Relevance
“…Kobold et al suggested the possibility of using IP anti-VEGF in the palliative treatment of malignant ascites [14]. A few studies have reported the effectiveness of IP bevacizumab in treating symptomatic malignant ascites, especially in ovarian cancer [19][20][21][22], with improved quality of life and reduced paracentesis. This treatment has been proposed only in palliative care, and complete response versus ascites has been reported [19], suggesting the efficacy of IP administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kobold et al suggested the possibility of using IP anti-VEGF in the palliative treatment of malignant ascites [14]. A few studies have reported the effectiveness of IP bevacizumab in treating symptomatic malignant ascites, especially in ovarian cancer [19][20][21][22], with improved quality of life and reduced paracentesis. This treatment has been proposed only in palliative care, and complete response versus ascites has been reported [19], suggesting the efficacy of IP administration.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported the effectiveness of IP bevacizumab in treating symptomatic malignant ascites, especially in ovarian cancer [19][20][21][22], with improved quality of life and reduced paracentesis. This treatment has been proposed only in palliative care, and complete response versus ascites has been reported [19], suggesting the efficacy of IP administration. In the curative therapeutic strategy for PSM, a new treatment combination must be developed to increase local control.…”
Section: Discussionmentioning
confidence: 99%
“…Kobold et al 12 reported that the therapeutic effect of intraperitoneal cisplatin was potentiated by BEV in a mouse model. Bellati et al 13 reported that the use of intraperitoneal BEV was associated with an increase in the proportion and function of CD8 effector T cells, and a reduction in circulating T(reg) cells, as well as resolution of malignant ascites in women with recurrent ovarian cancer. Similar therapeutic effects in humans have been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Notable in this regard is bevacizumab, an anti-vascular endothelial growth factor antibody now shown to effect clinical benefit in OC as both a single agent and in combination with other treatments [122], but which could also have substantial immune properties, including increasing interferon-γ production and inhibiting Treg generation. Sorafenib, a multi-tyrosine kinase inhibitor useful in OC likewise can inhibit Treg generation [102].…”
Section: Off-target Immune Effects Of Existing Agentsmentioning
confidence: 99%